(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 1993)
A biostratigraphical analysis of Jebel Tebaga (Tunisia) is given. The Permian is divided in two zones: Afghanella zone of Middle-Upper Murgabian age; and Neoschwagerina, Yabeina and Dunbarula zone of Upper Murgabian- Lower Midian age, himself divided in a lower subzone with Dunbarula nana and an upper subzone wirh Dunbarula mathieui and Codonofusiella.